A new intriguing species of the genus Pseudachorutella Stach, 1949 (Collembola: Neanuridae: Pseudachorutinae) from Kyrgyzstan with the supplementation of generic definition and the description of the first instar larva - Stryczek, Beata; Smolis, Adrian (Zootaxa, 2024)
Pseudachorutella intricata sp. nov. from Kyrgyzstan is described and illustrated in detail. Among known members of the genus, the new species is distinguished by a strong reduction of furca i.e. absence of mucro. In addition, the morphology of the first instar larva and the key to all Pseudachorutella from the Palearctic are provided.